Effects of Cement Content, Curing Period, Gradation, and Compaction Degree on Mechanical Behavior of Cement-Stabilized Crushed Gravel Produced via Vertical Vibration Test Method - Yingjun Jiang; Tian Tian; Changqing Deng; Kejia Yuan; Yong Yi (Advances in Civil Engineering)
In this paper, the reliability of vertical vibration test method (VVTM) was evaluated by comparing the changes in moisture content and gradation before and after forming the test piece by VVTM and static pressure method and the mechanical strength correlation between the laboratory compaction sample and the core sample in the field. The effects of cement content, curing period, gradation, and compaction degree on the unconfined compressive strength, splitting strength, and compressive rebound modulus of VVTM-compacted cement-stabilized crushed gravel (CSCG) were studied, and a mechanical strength prediction equation for VVTM-compacted CSCG was formulated. The results show that the correlation between the strength of the VVTM specimen and the field core sample can reach 92%; the mechanical strength of CSCG will increase with increase in the cement content, and when the cement content reaches approximately 4%, the increase in its mechanical strength will slow down; the mechanical strength of VVTM-compacted CSCG with different cement dosages and gradation types increased fast at 14 days of curing period and began to level off after 90 days. Compared with XM gradation, using GM gradation can improve the mechanical strength. Under different gradations and curing periods, the mechanical strength linearly increases with increase in the degree of compaction. The mechanical strength prediction equation has a high reliability; therefore, it can accurately predict the strength growth rules. Moreover, the degree of compaction increases by 1%, and the mechanical strength increases by approximately 10%.